THE ROLE OF INTERNATIONAL EDUCATION IN PROMOTING GLOBAL CITIZENSHIP - Jasur Ziyautdinov (TADQIQOTLAR.UZ, 2024)
Abstract: This article discusses the role of international education in promoting global citizenship.